The Study of Compressive Strength of Concrete in Case Study using Basalt Dust Aggregate from Nawarat Crushing Plant as Sand Replacement - Komenthammasopon, Surachai (Princess of Naradhiwas University Journal, 2020)
The research objectives were to investigate the compressive strength of the concrete, comprising partly in its mixture the basalt dust aggregate from Nawarat crushing plant as case study and to study its application in civil engineering. The basalt dust partially replaces quantity of sand in the concrete mixture were ranged from the ratio of 0, 20, 40, 60, 80, and 100 % (only basalt dust aggregate) by weight. The proportion of cement, sand and rock aggregate was 1:2:4 by weight and the water-cement ratio of the mixture (W/C) was 0.55. The slump of the partially-mixed concrete was 7.0-8.5 cm. The experimental results of this research project found that the compressive strengths at 28 days water curing for different proportions ranged from 173 to 229 kilograms per square centimeter (ksc) (or average value at 200 ksc). The outcomes also indicated that the concrete with 80 percentage of basalt dust in place of sand gave the highest compressive strength at 229 ± 2.90 ksc. The strength of normal concrete was 272 ksc which was higher than 15.8%, compared with the peak at 229 ksc of the partially mixed. For the application viewpoint, the standard of the Department of Public Works and Town & City Planning (DPT) 1101-52 had specified the lowest ultimate compressive strength at 150, 180, 210, and 240 ksc for the concrete type K1 (general civil construction) K2, K3 and K4. Thus, the strengths of concrete comprising of basalt dust as sand replacement for all proportions should comply the standard of concrete. The partly basalt mixed concrete therefore give high potential for the application in various civil constructions.